2015
DOI: 10.2147/tcrm.s93009
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of full and rapid neuromuscular blockade recovery with sugammadex in myasthenia gravis patients undergoing surgery – a series of 117 cases

Abstract: PurposeMyasthenia gravis (MG) is an autoimmune disease interfering with neuromuscular transmission. Patients are at risk of postoperative residual curarization (PORC) if nondepolarizing muscle relaxants are used. Clinically inapparent insufficient muscle strength may result in hypoventilation and postoperative bronchopneumonia. We describe a cohort of 117 cases in which sugammadex was used in MG patients undergoing surgery with muscle relaxation with rocuronium.Methods and patientsWe anesthetized 117 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…In one trial, NEO was administered at the reappearance of T 2 [49] f Bolus dose of VEC 0.1 mg/kg followed by maintenance with VEC 0.015 ng/kg as needed g Bolus dose of SUC 1.0 mg/kg bronchitis, chronic obstructive pulmonary disease) undergoing noncardiac surgery [56], patients with cardiac disease (i.e. ischaemic heart disease, chronic heart failure, arrhythmia) undergoing noncardiac surgery [57], patients with hepatic dysfunction (liver damage class B or C) undergoing hepatic surgery [58], morbidly obese patients (body mass index C40 mg/m 2 ; mean total bodyweight &130 kg) undergoing laparoscopic removal of gastric banding [59], and patients with myasthenia gravis undergoing surgical thymectomy or cholecystectomy [60]. Comparative trials were of randomized, safety assessorblind, multicentre design [56,57], randomized, singlecentre design [59] or nonrandomized, single-centre design [58].…”
Section: Special Patient Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In one trial, NEO was administered at the reappearance of T 2 [49] f Bolus dose of VEC 0.1 mg/kg followed by maintenance with VEC 0.015 ng/kg as needed g Bolus dose of SUC 1.0 mg/kg bronchitis, chronic obstructive pulmonary disease) undergoing noncardiac surgery [56], patients with cardiac disease (i.e. ischaemic heart disease, chronic heart failure, arrhythmia) undergoing noncardiac surgery [57], patients with hepatic dysfunction (liver damage class B or C) undergoing hepatic surgery [58], morbidly obese patients (body mass index C40 mg/m 2 ; mean total bodyweight &130 kg) undergoing laparoscopic removal of gastric banding [59], and patients with myasthenia gravis undergoing surgical thymectomy or cholecystectomy [60]. Comparative trials were of randomized, safety assessorblind, multicentre design [56,57], randomized, singlecentre design [59] or nonrandomized, single-centre design [58].…”
Section: Special Patient Populationsmentioning
confidence: 99%
“…Comparative trials were of randomized, safety assessorblind, multicentre design [56,57], randomized, singlecentre design [59] or nonrandomized, single-centre design [58]. Data in patients with myasthenia gravis were obtained from a case series [60]. The trials included adults who were ASA physical status I-III [58,59], II-III [56] or II-IV [57,60] and scheduled to receive general anaesthesia induced with propofol [57][58][59][60] and maintained with propofol [57,58], desflurane [59] or isoflurane [60], with opioids also permitted, or according to local practice [56].…”
Section: Special Patient Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For recovery from anesthesia in patients with MG, some author recommended using sugammadex as a safe and reliable option for reversal of neuromuscular blocker in patients with MG [3,11,16], whether or not to reverse residual neuromuscular blockade at the end of surgery is controversial [8].The administration of sugammadex for reversal of neuromuscular blocker is useful to eliminate the risk of residual neuromuscular blockade in patients with MG [17]. Most case reports showed that neuromuscular blocker reversal using sugammadex seemed to be a safe, rapid, efficient, and reliable option without signs of postoperative residual neuromuscular block in patients with MG [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%